Hume on God irony, deism and genuine theism - Yoder, Timothy S. (London ; New York : Continuum, 2008)
Re-examining his writings on religion, this book investigates Hume's use of irony and his relationship with the Deists of his era.
The conventional story of Hume on God -- Hume and irony -- Hume and Deism -- Hume on the existence of God -- Hume on the nature of God.
Includes bibliographical references (p. [147]-161) and index.
Description based on print version record.
Keywords: Hume, David, -- 1711-1776 -- Religion; God -- History of doctrines -- 18th century; Religion; RELIGION -- Agnosticism; Hume, David; Religionsphilosophie; Gottesvorstellung; Electronic books